African Migration to Israel: Debt, Employment and Remittances - Furst-Nichols, Rebecca; Jacobsen, Karen (Tufts Archival Research Center, 2005)
This report details the migration experience and livelihood choices of Sudanese and Eritrean asylum seekers and migrants in Tel Aviv. The research is based on a scoping study conducted by a Feinstein Researcher, Rebecca Furst-Nichols, in November-December 2010. Since 2007, an increasing number of African migrants and asylum seekers have been smuggled across the Egyptian Sinai into Israel. Today, there are nearly 35,000 non-Jewish African migrants living in Israel, the majority Eritrean and Sudanese. The report provides an overview of Israeli policy toward African migrants and asylum seekers, routes taken to Israel, experience with Bedouin smugglers, employment opportunities, legal status, protection issues, and the role of remittances in repaying smuggling debt to family and friends in the diaspora.